Forest species extracts as an alternative control for tiririca (Cyperus rotundus) - Silveira, Flávio Pereira da Mota; d’Antonino, Leonardo; Rocha, Igor Tenório Marinho da; Lins, Hamurábi Anizio; Albuquerque, José Ricardo Tavares de; Souza, Matheus de Freitas (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The objective of this study was to evaluate the allelopathic effect of leaf extracts of the forest species leucena and algaroba at different concentrations on the germination and initial growth of Cyperus rotundus weed. The experiment was conducted in a completely random design with a 3 x 4 factorial arrangement, with four replications. The first factor was represented by two types of forest species leaf extracts: algaroba (Prosopis juliflora) and leucena (Leucaena leucocephala), and a level without application of the extract. The second factor was represented by four different concentrations of each extract, 25%, 50%, 75%, and 100% p v-1. The number of sprouts emerged each day, emergence percentage after 21 days of planting, seedling emergence speed index, seedling length, fresh matter and dry matter of shoots were evaluated. There was a significant (p<0.05) effect of the extracts and their concentrations on the growth of the weed plant, interfering in the shoot length of the Cyperus rotundus weed seedlings, and significant effect (p<0.01) of the extracts on the fresh mass and total dry shoot. However, the other parameters were not influenced by the extracts types and concentrations. The effectiveness of extracts of forest species, algaroba and leucena, as bioherbicides in the control of Cyperus rotundus weed plants was not proved.